Structural Insights into the Chaperone Activity of the 40-kDa Heat Shock Protein DnaJ: BINDING AND REMODELING OF A NATIVE SUBSTRATE - Cuéllar, Jorge (American Society for Biochemistry and Molecular Biology, 2013)
Hsp40 chaperones bind and transfer substrate proteins to Hsp70s and regulate their ATPase activity. The interaction of Hsp40s with native proteins modifies their structure and function. A good model for this function is DnaJ, the bacterial Hsp40 that interacts with RepE, the repressor/activator of plasmid F replication, and together with DnaK regulates its function. We characterize here the structure of the DnaJ-RepE complex by electron microscopy, the first described structure of a complex between an Hsp40 and a client protein. The comparison of the complexes of DnaJ with two RepE mutants reveals an intrinsic plasticity of the DnaJ dimer that allows the chaperone to adapt to different substrates. We also show that DnaJ induces conformational changes in dimeric RepE, which increase the intermonomeric distance and remodel both RepE domains enhancing its affinity for DNA.